2021
DOI: 10.7717/peerj.12035
|View full text |Cite
|
Sign up to set email alerts
|

To culture or not to culture: a snapshot of culture-dependent and culture-independent bacterial diversity from peanut rhizosphere

Abstract: Background Sequencing driven metagenomics studies have been instrumental in various aspects of microbiology including identification of newer taxa. While this culture-independent approach has its own merits and demerits, several studies have focussed on comparing it with traditional culture-dependent (CD) approach. However, most of these comparative studies rely on Sanger sequencing of complete 16S rRNA gene from pure culture colonies to determine the culturable bacterial diversity. This approach undercounts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This might be due to the very low abundance of those organisms, which is a limitation of CI approach. Comparing all the genera of both the approaches, revealed that total 38 genera were exclusively found in CD samples, that is similar to the studied by Hinsu et al 57 . Most of these genera are commonly found in soil, forest and water sources including marine water.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This might be due to the very low abundance of those organisms, which is a limitation of CI approach. Comparing all the genera of both the approaches, revealed that total 38 genera were exclusively found in CD samples, that is similar to the studied by Hinsu et al 57 . Most of these genera are commonly found in soil, forest and water sources including marine water.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, for comparative study, partial 16S rRNA gene was sequenced, similar to metagenomics, rather than sequencing the entire 16S rRNA gene, through Sanger sequencing as done in all previous researches 32 34 . As per our knowledge, a similar approach has also been successfully applied by Zehavi et al for the study of ruminal microbiota and in our previous study on rhizosphere microbiome 56 , 57 . This approach could be helpful to analyze the presence-absence based study of microbial diversity.…”
Section: Discussionmentioning
confidence: 88%
“…One reason could be the recovery medium used for culture-dependent isolation was unsupportive of Lactococcus spp. Some investigators have examined as many as four [62] to eight [63] growth media for comparison with culture-independent methods for improved detection of OTUs. Anguita-Maeso et al (2020) examined xylem-colonizing bacteria of olive plants and found only 41% of the total genera using culture-dependent methods as was found by culture-independent methods by Illumina MiSeq 16S rRNA sequencing using NGS [62].…”
Section: Changes In the Microbial Community During Processingmentioning
confidence: 99%
“…However, these techniques have well-known limitations. For instance, many species remain undetected because appropriate culture conditions are either unknown or challenging to reproduce [ 41 ] . Moreover, culture methods are time-consuming and hardly suitable for high-throughput analysis.…”
Section: Characterising the Mycobiome: Identification And Technologic...mentioning
confidence: 99%